PENGARUH PEMAHAMAN DASAR AKUNTANSI KEUANGAN DAN KEMAMPUAN MENGGUNAKAN KOMPUTER TERHADAP PRESTASI BELAJAR KOMPUTER AKUNTANSI PADA MAHASISWA PROGRAM STUDI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ISLAM MALANG - Panetep Bagus Samudra; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine the effect of basic understanding of financial accounting and the ability to use computers on learning achievement of accounting computers in accounting study program students, Faculty of Economics and Business, Islamic University of Malang. The population in this study were students of the accounting study program, Faculty of Economics and Business, Islamic University of Malang. The sample used is part of the accounting students of the Faculty of Economics and Business, Islamic University of Malang. The technique used in sampling was purposive sampling technique, with 103 students selected as a sample. The data were collected using a questionnaire method. The data analysis method used is multiple regression analysis with the help of SPSS software version 14 (Statistical Products and Service Solutions version 14). The test data used were simultaneous hypothesis testing (f), determination coefficient (R2), and partial hypothesis testing (t). The results showed that the independent variable simultaneously had a significant effect on the dependent variable. Based on the coefficient of determination test results, the value of R2 Square is 53.6% while the remaining 46.4% is influenced by other variables not included in this study. Based on the results of the partial test, the variables of basic understanding of financial accounting (sig = 0.000) and the ability to use computers (sig = 0.004) have an effect on the learning achievement of accounting computers.Keywords: basic understanding of financial accounting, ability to use computers and learning achievement of accounting computers